Management of large periapical lesion due to trauma using triple antibiotic paste - Abidin Talha Mutluay; Merve Mutluay (Wolters Kluwer Medknow Publications, 2017)
Introduction: Mechanical instrumentation and chemical irrigation alone is not considered enough to eliminate microorganisms in the deeper layer of root canal system. Therefore, antibacterial medicaments are required for complete disinfection of root canal dentin. Case Presentation: Triple antibiotic paste application (metronidazole, ciprofloxacin and minocycline) have demonstrated good clinical and radiographical results for treatment of presented traumatized teeth with periapical lesion. Conclusion: It confirms that conservative treatment should be first option for treatment of periapical lesion. Triple antibiotic paste has benefical effects for traumatized teeth with periapical lesion.